Parole work in Canada: caseloads, cultures, and carceral spaces - Ricciardelli, Rose (Rowman & Littlefield, 2024)
"This resource advances the scholarship in academic research about the experiences of parole officers' occupational challenges, including exposure to potentially psychologically traumatic events, and provides evidence-based recommendation for meeting the mental health needs of correctional workers broadly"--